Nasopharyngeal and Peripheral Blood Type II Interferon Signature Evaluation in Infants during Respiratory Syncytial Virus Infection - Savino, Francesco; Dini, Maddalena; Clemente, Anna; Calvi, Cristina; Pau, Anna; Galliano, Ilaria; Gambarino, Stefano; Bergallo, Massimiliano (Medicina (Kaunas, Lithuania), 2024)
Background and Objectives: In this study, we applied one-step real time rt-PCR technology type II INF signature to blood and nasopharyngeal (NPS) swabs of acute early recovery children < 1 years hospitalized for bronchiolitis with laboratory-confirmed RSV infection. Materials and Methods: A prospective observational case–control study was conducted in 2021–2022. The study took place in Children Hospital “Regina Margherita”, Torino Italy. The study included 66 infants, of which 30 patients were hospitalized for bronchiolitis due to RSV infection and 36 age-matched controls. Inclusion criteria included a positive RSV test for infants with bronchiolitis. We collected peripheral blood and nasopharyngeal swabs for relative quantification of type II Interferon signature by One-Step Multiplex PCR real time. Results: IFN levels were downregulated in the peripheral blood of bronchiolitis patients; these data were not confirmed in the nasopharyngeal swab. There was no correlation between NPS and the type II IFN score in peripheral blood. Conclusions: our study shows for the first time that type II IFN score was significant reduced in peripheral blood of infants with bronchiolitis by RSV compared to age-matched healthy controls; in the NPS swab this resulted downregulation was not statistically significant and the type II IFN score in the NPS swab can be used as marker of resolution of infection or improvement of clinical conditions.